Sexual offending and mental health: multi-disciplinary management in the community - Houston, Julia (Forensic focus, 2008)
Part I: Theoretical perspectives -- An overview of sexual offending / Julia Houston -- Risk assessment / Jackie Craissati -- Mental disorder and sexual offending / Andrew M. Aboud -- Sexual offending : ethnicity, culture and diversity issues in assessment and management / Olumyiwa John Olumoroti -- The law and sex offending / Sarah Galloway and Sandra MacPhail -- Part II: Clinical practice issues -- A sex offender service within a mental health setting / Julia Houston and Malcolm Scoales -- Clinical assessment and formulation / Tim Green -- Treatment, relapse prevention, and building good live / Tim Green -- The impact of personality disorder on working with sexual offenders / Sharon Prince -- Multi-agency/disciplinary working with sexual offenders / Sarah Galloway and Adina Seupersad -- The non-abusing parent and their role in risk management / Sarah Galloway and Natalie Hogg -- Systematic interventions with sexual offending / Alison Beck -- The impact on professionals of working with sex offenders / Sharon K.C. Leicht